2014
DOI: 10.1002/2013jb010500
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the shallow velocity structure of the Lucky Strike Volcano, Mid-Atlantic Ridge, from downward continued multichannel streamer data

Abstract: The shallow velocity structure of the Lucky Strike segment of the Mid-Atlantic Ridge is investigated using seismic refraction and reflection techniques applied to downward continued multichannel streamer data. We present a three-dimensional velocity model beneath the Lucky Strike Volcano with unprecedented spatial resolutions of a few hundred meters. These new constraints reveal large lateral variations in P wave velocity structure beneath this feature. Throughout the study area, uppermost crustal velocities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 83 publications
(202 reference statements)
1
39
0
Order By: Relevance
“…Arnulf et al () and Arnulf, Harding, Kent, Singh, et al () showed that the combination of a SOBE method and 3‐D traveltime tomography enables proper imaging of the high‐velocity gradient region at the base of layer 2A. The layer 2A thickness map of Figure a represents a smoothed surface corresponding to a velocity gradient of ~3/s and was created from picks on crossing vertical profiles extracted from the tomographic structure (solid blue lines in Figures c and d).…”
Section: Tomography Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Arnulf et al () and Arnulf, Harding, Kent, Singh, et al () showed that the combination of a SOBE method and 3‐D traveltime tomography enables proper imaging of the high‐velocity gradient region at the base of layer 2A. The layer 2A thickness map of Figure a represents a smoothed surface corresponding to a velocity gradient of ~3/s and was created from picks on crossing vertical profiles extracted from the tomographic structure (solid blue lines in Figures c and d).…”
Section: Tomography Resultsmentioning
confidence: 99%
“…We then performed 3‐D linearized tomographic inversions of the combined 473,853 crustal OBS and SOBE Pg‐phases following the methodology of Arnulf, Harding, Kent, Singh, et al (), specific to SOBE MCS data, which was adapted from the Van Avendonk et al () approach for OBS data. The forward model was calculated using a shortest path method (Moser, ) with additional corrections to reduce traveltime errors associated with the discretization of the seafloor bathymetry.…”
Section: Tomography Data and Methodsmentioning
confidence: 99%
“…Resolution at the top of oceanic crust within the velocity models that make up the compilation is often low due to the lack of first‐arrival energy for rays that turn within the uppermost region (e.g., Ewing & Purdy, ). Higher resolution in the upper crust can be achieved by using long streamer data from seismic reflection studies, especially if data is downward continued to near the seafloor (Arnulf et al, ; Arnulf et al, ; Arnulf et al, ; Henig et al, ; Kardell et al, ; Nedimović et al, ); however, these studies do not provide full crustal‐scale velocity models and are not included in our compilation. High‐resolution upper crustal studies typically show low velocities within layer 2A near the seafloor with a high‐gradient region at the layers 2A and 2B boundary.…”
Section: Discussionmentioning
confidence: 99%
“…This limit corresponds to the northernmost corrugation ridge in the bathymetry, Figure b, and to the limit inferred from gravity modeling [ Blackman et al ., ]. The small hill at 3 km distance is the southern limit of the surficial volcanics as inferred from side scan sonar imaging [ Blackman et al ., ], and the velocity model shows the development of a thin, 0.1 km thick, surface layer with a basement velocity of 2.5 km/s (Figure b), a value typical of seismic layer 2A and volcanics in young crust [e.g., Arnulf et al ., ]. Below the surface layer, velocities and gradients are similar to those of the Southern Ridge, but ∼0.5–1 km/s faster than those measured in the adjacent hanging wall block and in the conjugate volcanic crust, east of the MAR axis [ Henig et al ., ].…”
Section: Discussionmentioning
confidence: 99%